Economic Considerations in the Design of Ocean Observing Systems - Hauke L. Kite-Powell (Oceanography, 2009)
Recent work on the potential economic value of improved coastal ocean observing capabilities suggests that aggregate values of better ocean observing system information for all US waters could be in the hundreds of millions of dollars per year. This aggregate value derives from specific information delivered to particular user groups in particular regions; the scale of benefits depends on the economic importance of the user sectors and on their ability to make use of better information about local and regional marine conditions. As we continue to refine these estimates of economic value, information on benefits is becoming sufficiently specific to be useful in the observing system design process. This paper describes a National Oceanographic Partnership Program study on the economics of ocean observing system information, presents a framework for incorporating economic information into observing system design, and sketches the beginning of an application of this process to the northeast region of the United States.